An analysis of the fate of 917 manuscripts rejected from Clinical Otolaryngology. (18th January 2017) - Earnshaw, C.H.; Edwin, C.; Bhat, J.; Krishnan, M.; Mamais, C.; Somashekar, S.; Sunil, A.; Williams, S.P.; Leong, S.C.
Abstract : Objectives: The fate of all manuscripts rejected from the journal Clinical Otolaryngology ( CO ) over a three‐year period was investigated. The aim was to review publication rate, delay and the impact factors of the journals that the papers went on to be published in. Design: In total, 917 papers were rejected from CO between 2011 and 2013. The fate of these manuscripts was determined by searching for the corresponding author's surname, and if necessary keywords from the manuscript title, in both PubMed and Google Scholar. Main outcome measures: The main outcome measures recorded were as follows: the subsequent publication of the article, delay to publication and journal of publication. Results: In all, 511 papers were subsequently published in journals, representing 55.7% of all rejected manuscripts. The average delay was 15.1 months (standard deviation [sd ] = 8.8). The impact factor of CO was found to be higher than the average of the journals that accepted the rejected manuscripts in all 3 years. Only 41 (8%) papers were published in journals with a higher impact factor than CO . Of all subsequently accepted manuscripts, 60 (11.7%) were found only on Google Scholar (and not on PubMed). Conclusions: Rejection from CO certainly does not prevent subsequent publication, although the papers tend to be published after a lengthy delay and in journals with a lower impact factor than CO . When performing literature searches, it is important to search more than one database to ensure as many of the relevant articles are found as possible.